Effects of maternal exposure to fine particulate matter on birth weight in 16 counties across China: a quantile regression analysis. (4th May 2021) - Wu, Kaipu; Hu, Huanqing; Ren, Zhoupeng; Benmarhnia, Tarik; Ren, Meng; He, Simin; Knibbs, Luke D; Meng, Xia; Di, Jiangli; Huang, Cunrui; Wang, Qiong
Abstract: The adverse effects of air pollution during pregnancy have been studied intensively, but mainly utilizing linear and logistic models, which generally yield little information about how air pollution may change the distribution of birth weight in populations. We aimed to examine the effects of fine particulate matter (PM2.5 ) on quantiles of birth weight, and if effects were heterogeneous in different populations and regions. We used a prospective cohort study of 196 283 singleton term live births from 16 counties across China during 2014–2018. PM2.5 exposure for full gestation, each trimester and last gestational month were assessed by Inverse Distance Weighting interpolation. Linear and quantile regression were conducted to estimate associations between PM2.5 exposure and mean birth weight, as well as birth weight distribution, with birthweight z -score as the main outcome. Stratified analyses and Cochran Q tests were conducted by maternal and geographical characteristics. Each 10 µ g m −3 increase in average PM2.5 over the entire pregnancy was associated with reduced birthweight z -score (−0.010, 95% CI: −0.015, −0.005) and birth weight (−3.21 g, 95% CI: −5.27, −1.15). In quantile regression, more pronounced effects were observed in lower and intermediate quantiles, with a decrease of 0.021 (95% CI: 0.033, 0.009) and 0.009 (95% CI: 0.015, 0.002) in the 5th and 50th quantiles of birthweight z -score, respectively. Additionally, we observed stronger associations among well-educated, migrant and primiparous mothers as well as in coastal areas. Maternal exposure to PM2.5 was associated with reduction in birth weight, especially for those with very low birth weight. Well-educated, migrant and primiparous mothers, as well as births in coastal areas may be more sensitive to PM2.5 in our study population. The results may be relevant to targeted public health interventions to reduce maternal exposure to air pollution.